A novel and cost-effective hardening technology for tissue-cultured banana - Mishra, Maneesh; Sharma, Priti; Rajan, Shailendra; Damodaran, T (Indian Horticulture, 2024)
Micropropagation of banana has attained industrial status and millions of plants are produced every year using this technology. However, acclimatization of tissue cultured plants is the most crucial step where 5-8% mortality is observed. Primary hardening is usually done in portrays and each tray can accommodate around 98 plants. This system of primary hardening not only allows higher mortality rate but it adds to cost of transportation and leave carbon foot print. We describe a cost-effective and less time consuming hardening technology of tissue-culture banana using polypropylene bags which are not only handy in operation and transport but they are cost effective and gives up to 98% survival during long distance transport.